Suprachiasmatic to paraventricular nuclei interaction generates normal food searching rhythms in mice - Olejniczak, Iwona; Campbell, Benjamin; Tsai, Yuan-Chen; Tyagarajan, Shiva K.; Albrecht, Urs; Ripperger, Jürgen A. (Frontiers in Physiology, 2022)
Searching for food follows a well-organized decision process in mammals to take up food only if necessary. Moreover, scavenging is preferred during their activity phase. Various time-dependent regulatory processes have been identified originating from the suprachiasmatic nuclei (SCN), which convert external light information into synchronizing output signals. However, a direct impact of the SCN on the timing of food searching has not yet been found. Here, we revisited the function of the SCN to affect when mice look for food. We found that this process was independent of light but modified by the palatability of the food source. Surprisingly, reducing the output from the SCN, in particular from the vasopressin releasing neurons, reduced the amount of scavenging during the early activity phase. The SCN appeared to transmit a signal to the paraventricular nuclei (PVN) via GABA receptor A1. Finally, the interaction of SCN and PVN was verified by retrograde transport-mediated complementation. None of the genetic manipulations affected the uptake of more palatable food. The data indicate that the PVN is sufficient to produce blunted food searching rhythms and is responsive to hedonistic feeding. Nevertheless, the search for normal food during the early activity phase is significantly enhanced by the SCN.